Polymorphism of the rps16 gene intron in Malus Mill. and related Rosaceae Juss. species - M. A. Filyushin (Vavilovskij Žurnal Genetiki i Selekcii, 2017)
The intron of the chloroplast rps16 gene encoding ribosomal protein 16S belongs to group II introns, which have the capacity to self-splice. The sequence of this intron may be quite polymorphic and is widely used for molecular-genetic studies of different plant families. But regions of the intron important for splicing and organization of the pre-mRNA secondary structure in Rosaceae species including the genus Malus have not yet been described.The aim of the work was to characterize the nucleotide sequences of the rps16 gene intron, to study their polymorphism and to identify the individual structural elements of the intron determining the correct splicing of the rps16 gene in Malus species and related Rosaceae species. Nucleotide sequences of the rps16 chloroplast gene group II intron from 32 Malus species and 17 related Rosaceae species were amplified, sequenced and their polymorphism was analyzed. The rps16 intron sequence in the genus Malus appeared to be very conservative (1.5 %), as well as in Prunus species, the level of the rps16 intron polymorphism was slightly higher (2.25 %). In the studied sequences the boundaries of the six functional domains typical of group II introns and IBS/EBS binding sites were identified. Variability of all the domains and inter-domain regions was studied. Domains V and VI were the most conservative, which may be due to their role in the positioning of the pre-mRNA structures and formation of the catalytically active secondary structure. Thus, polymorphism of the rps16 gene intron was for the first time studied in Malus species and related Rosaceae species. The boundaries of all six functional domains typical of group II introns and IBS/EBS binding sites were identified. The most conservative were domains V and VI.